A Study on the Factors Affecting Consumer Buying Behavior towards Online Shopping in Pakistan - Ahmed, Zahid; Su, Ling; Rafique, Kalsoom; Khan, Sher Zaman; Jamil, Sadaf (Journal of Asian Business Strategy, 2018)
The present study is concerned in the field of consumer buying behavior, especially e-shopping in Pakistan. E-commerce has created easiness and innovativeness in humans’ life. Online consumer buying behavior is not like a physical market having ability to touch, analyze, and thereafter shop the products. This study explores the effect of few variables, derived from existing literature. Those variables are perceived benefits, domain specific innovativeness, and shopping orientations, i.e., impulse-purchase orientation, brand orientation and quality orientation. The data was collected by mean of the questionnaires. The findings indicated that domain specific innovativeness and shopping orientations have positive impact on consumers’ buying behavior towards online shopping. Therefore, consumers are showing an interest to online shopping because of recent development of electronic stores in Pakistan.